Determinan Keputusan Pembelian Pakaian Bekas Impor: - Hasibuan, Indra Mualim; Erianto, Ridho; Batubara, Chuzaimah (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Minister of Trade No. 40 of 2022, stipulates the activity of thrifting as a prohibited activity, with the consideration that one of them is disrupting the domestic textile industry, from a health perspective, users are susceptible to skin disease infections. However, government bans and studies on the adverse effects of imported used clothing on health have not necessarily reduced millennial interest in buying imported used clothing. Consumption of imported used clothing is very popular among millennials, based on a survey conducted including a good stats survey and researchers' initial observations. This study aims to determine the partial and simultaneous effect of price, product knowledge, and product quality on the purchase decision of imported used clothing. This study uses a quantitative approach. The type of data used is secondary data using a questionnaire technique. The research population was students of FEBI UINSU, using a sample of 100 respondents. Data analysis technique; validity test, reliability test, classic assumption test, hypothesis test, multiple linear regression test, coefficient of determination test using SPSS 26 software. The results of the research variable Price partially have no effect on Purchase Decisions. Product Knowledge and Product Quality partially influence Purchasing Decisions. Simultaneously the independent variables affect the dependent variable. Independent variables are able to explain the dependent variable by 30.7%, the remaining 69.3% is explained by other variables outside the study. Keywords: Price, Product Knowledge, Product Quality, Purchase Decision